EFEKTIVITAS BADAN PENGHUBUNG DALAM MEMFASILITASI URUSAN PEMERINTAH DAERAH DAN PEMBANGUNAN KEPADA PEMERINTAH PUSAT - Ruhut Novum S.R Simanullang; Rayhan Ahmad Adimulyo; Satrio Panji Wisesa; Sulistia Wardani; Muhammad Faisal (Jurnal Pallangga Praja (JPP), 2022)
Jawa Barat Government Liaison Agency, is a Regional agency which is only located in theCapital City, after the establishment of the Jawa Barat Government Liaison Agency as afacilitator of regional needs in collaborating with the central government, researchers want toknow how the effectiveness of the Jawa Barat Government Liaison Agency in facilitating JawaBarat Government affairs to The Central Government in helping to advance the developmentof the Jawa Barat Region, this research was conducted using a qualitative descriptivemethod, the results of the study showed 1)Organizational characteristics of the Jawa BaratGovernment Liaison Agency consistingof the Head of the Agency led by Echelon III, theAdministration Sub-Sector, the Inter-Relations Sub-Sector, the Promotion and InformationSub-Sector, the Protocol Sub-secto, which are entirely led by Echelon IV. 2)Environmental Characteristics The Jawa Barat Government Liaison Agency is within the scope of cityadministration which is very close to the central government. 3) Characteristics of workers,most of the employees come from the Jawa Barat region who have the same customary andcultural values. 4) Management Policies and Practices in the 2017-2022 Strategic Plan arestated as local government policies informulating efforts to develop Jawa Barat areas whichpoint to the realization of reforms. quality bureaucracy, the realization of an Islamic culturalsystem, customs and arts, the realization of integrated information and data.